Pollination success of Fraxinus excelsior L. in the context of ash dieback - Eisen, Anna-Katharina; Semizer-Cuming, Devrim; Jochner-Oette, Susanne; Fussi, Barbara (Annals of forest science., 2023)
KEY MESSAGE: Paternity analyses show that effective pollination of ash (Fraxinus excelsior L.) in a seed orchard and a floodplain forest affected by ash dieback is more likely to be facilitated by healthier males. Thereby, natural selection can have a positive effect on the health of future generations. CONTEXT: Ongoing ash dieback and increasing fragmentation of ash populations may result in reduced pollen flow, which can reduce pollination success of future generations of ash trees. Therefore, it is essential to further improve our understanding of gene flow patterns, especially with respect to ash dieback. AIMS: In this study, paternity analyses were conducted in a seed orchard and a floodplain forest in Germany in 2018 to explain the relationship between pollination success and the health status of ash trees and distances of effective pollen transport. METHODS: Cambium samples (i.e., from twigs and stumps) were collected from 251 ash trees (putative father and mother trees) for genotyping, and the health status of each tree was documented using a scoring system to evaluate vitality. Additionally, seeds were harvested from 12 mother trees per site. Genetic analyses using nuclear microsatellites were performed to determine paternal trees. Paternities were assigned based on the likelihood model implemented in the Cervus 3.0.7 software. RESULTS: Our results showed that the average pollination distance was 76 m in the seed orchard and 166 m in the floodplain forest. In general, pollination success decreased substantially with increasing distance to the mother tree. Despite the dense tree cover in the floodplain forest, pollen were transported over long distances (greater than 550 m), suggesting that non-local sources also play a role in pollination. This is supported by the foreign pollen input identified in the seed orchard (66.5%). Self-pollination was detected only to a very small extent, and thus had no major influence on reproduction. In addition, both healthy and slightly diseased father trees showed similar mating success. However, this was not the case for the severely diseased ash trees (more than 50% of crown damage) because only a few offspring could be assigned to them. Nevertheless, in contrast to the floodplain forest, there was no significant correlation between damage classes and pollination success in the seed orchard. CONCLUSION: Long-distance pollen transport contributes to the connectivity of ash trees in the landscape. Additionally, both healthy and slightly diseased fathers have a greater contribution to pollination, thus potentially improving the health of the next generation of ash trees. Moreover, gene flow between stepping stone populations is necessary to ensure the positive impact on the genetic diversity of ash populations in the future.